Wellness Programs and the Effects on Job Satisfaction - Jeffers, Alexiss; Jirschele, Kendra; O'Hearn, Molly; Palmer, April; Wichman, Alyssa (My University, 2013)
Research has shown there is an association between existence of wellness programs and job satisfaction, because worksite wellness programs create positive attitudes and make employees happier (Parks & Steelman, 2008). Although a clear link has been established between provision of wellness programs and job satisfaction, less is known about other variables that may mediate this relationship. The purpose of this study was to examine the potential mediating factors of source of support, channel of communication and perceived organizational intent on offering wellness programs on the relationship of the existence of the wellness program and job satisfaction.
Color poster with text, images, and tables.
Keywords: Employee health promotion; Job satisfaction; Posters